Pemerahan dan Penundaan Penjepitan Tali Pusat terhadap Kadar Hemoglobin Bayi Baru Lahir - Ahmaniyah Ahmaniyah; Kamilah Hidajati; Ari Suwondo (Journal of Ners and Midwifery, 2018)
The incidence of iron deficiency anemia in term infants from 0-6 months is 40.8%. Efforts to reduce anemia in infants and toddlers is by ensuring the baby gets blood from the placenta through the umbilical cord. Labor occurs when oxygen shifts from the heart to the lungs 8-10% of the fetal period to 50% in neonates. Immediate cord clamping vascular resistance from the disconnected placenta which results in the increased of resistance of the baby's vascular system and eliminates about 1/4 of the volume of blood and iron in the neonate. The time of cutting the umbilical cord is a determining factor for placental transfusion to the baby. Delay cord clamping and umbilical cord milking are expected to provide iron reserves in infant. The aim of this study was to determine the differences in umbilical cord milking and delayed cord clamping. The design used experimental study with posttest-Only Control Group. The sampling technique used simple random sampling differs into treatment group and control group. The treatment group was umbilical cord milking and the control group was delayed cord clamping. The highest average of Hb levels in the umbilical cord milking group was 17.3mmHg and the delayed cord clamping group was 15.75 mmHg. Difference test on umbilical cord milking group and delayed cord clamping group used independent T-test obtained P <0.05 (p = 0,001). It is recommended that midwives used umbilical cord milking as an alternative action in providing midwifery care to newborns when clamping and cutting the umbilical cord. It was proven that there were differences in the haemoglobin levels of newborns between the umbilical cord milking group and delayed cord clamping group.